The Effect of Work Environment and Work Stress on Employee Performance at PT Bhineka Cipta Karya - Siam Siawati; Asep Jamaludin; Yeni Fajrin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the results of the function area and many functional thoughts to the performance of the workforce at PT. Bhineka held a Karya. The research method used is a quantitative approach using census procedures with all populations as respondents. Data collection was carried out by distributing a Google Form-based questionnaire distributed with WhatsApp groups by obtaining 100 respondents with the full number of PT. Diversity of Works. The research instrument has been tested for legality and reliability to ensure the reliability of the data. Data analysis used t-test, F test, and multiple linear regression. A determination coefficient (Adjusted R Square) of 0.692 indicates that 69.2% of the variation in labor performance can be explained by functional areas as well as many functional minds, while the remaining 30.8% are influenced by other factors not accounted for in this study model. The results of the study tell that the functional environment has a positive and significant influence on employee performance, while many functional thoughts have a negative and important influence on the performance of the workforce, in a simultaneous way, the work environment and many work thoughts affect the performance of the workforce.